2014
DOI: 10.1136/heartjnl-2013-305296
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of secondary prevention medications, lifestyle advice, and referral to rehabilitation among acute coronary syndrome inpatients: results from a large prospective audit in Australia and New Zealand

Abstract: ObjectiveTo evaluate the proportion of patients hospitalised with acute coronary syndrome (ACS) in Australia and New Zealand who received optimal inpatient preventive care and to identify factors associated with preventive care.MethodsAll patients hospitalised bi-nationally with ACS were identified between 14–27 May 2012. Optimal in-hospital preventive care was defined as having received lifestyle advice, referral to rehabilitation, and prescription of secondary prevention pharmacotherapies. Multilevel multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 19 publications
8
101
2
Order By: Relevance
“…Patients undergoing PCI were most likely to receive DAPT, an observation consistently reported in other observational studies [5,8], and reflects the accepted view of DAPT following coronary stenting for the vast majority of PCI patients.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Patients undergoing PCI were most likely to receive DAPT, an observation consistently reported in other observational studies [5,8], and reflects the accepted view of DAPT following coronary stenting for the vast majority of PCI patients.…”
Section: Discussionsupporting
confidence: 49%
“…Yet as recently as 2012, a comprehensive Australian and New Zealand audit encompassing over 90% of hospitals across both countries showed that only 63% of ACS patients received a second antiplatelet agent at hospital discharge [8]. In all reported studies, one consistent observation was the difference between prescription of a second antiplatelet for patients following PCI (percutaneous coronary intervention), where rates were higher than for those undergoing CABG or medical management, despite a consistent accumulation of evidence supporting the use of these second agents in each of these contexts [9][10][11] There remains a significant risk of events following an ACS, with mortality in the [12][13][14][15][16][17][18] months following an ACS reported to be 12.6%, and the composite rate of myocardial infarction, stroke or cardiovascular death to be 18.3% [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This trend was similar to that of inpatient CR use, and was consistent with that noted in previous studies. 10,22, 32 These findings suggested that the diagnosis at admission persistently influences the subsequent utilization of CR. As national and international guidelines recommend CR for patients diagnosed with angina and MI, 6-8 the promotion of CR among this patient population is a common challenge worldwide.…”
Section: Factors Related To Cr Usementioning
confidence: 83%
“…This approach is recommended for the management of patients with chronic heart failure (CHF) (Selig et al, 2010) and has been shown to increase exercise capacity (Lewinter et al, 2014;Rees et al, 2004), improve quality of life and reduce hospitalisations (Taylor et al, 2014). Despite this overwhelming benefit, there is still an under-utilisation of exercise-based rehabilitation programs across the world (Pack et al, 2015;Piepoli et al, 2015;Redfern et al, 2014). Traditionally these programs are provided by healthcare professionals in centralised facilities .…”
Section: Chapter 7 Discussionmentioning
confidence: 99%
“…However, while these centre-based programs have been shown to be safe and effective (Smart & Marwick, 2004), they are of limited availability and yield low attendance rates. For instance, 46% of eligible patients with acute coronary syndrome had a documented referral to cardiac rehabilitation in Australia and New Zealand (Redfern et al, 2014), and only 30% of these patients actually participated in cardiac rehabilitation despite this being a recommended therapy (Doll et al, 2015;Suaya et al, 2007). In a systematic review of 34 qualitative studies of 1,213 patients, reported barriers for accessing these centre-based cardiac rehabilitation programs include lack of transport and parking, financial cost and competing work and carer commitments (Neubeck et al, 2012).…”
Section: Exercise and Chronic Heart Failurementioning
confidence: 99%